Estudo comparativo da degradação do inseticida Endosulfan através de: ozônio, fotólise e ozonização fotolítica - Curti, Karla Carvalho Fernandes (2011)
Aqueous solutions containing the insecticide Endosulfan was degraded using ozone, UV radiation and the ozone/UV radiation combined process. The ozone was generated electrochemically using a laboratory-made filter-press electrochemical reactor, represented by the cell diagram b-PbO2/Nafion®117/aço316. Ozone was applied under the semi-batch conditions using a column bubble reactor. A high-pressure mercury vapor lamp (HPL-N) 400 W, was used as a source of UV radiation. This lamp was inserted in a cylindrical annular reactor made of PVC (1.0 dm3). Degradation of Endosulfan was carried out in aqueous solutions (pH 5 and pH 12) and the reaction extent monitored by means of the UV spectrophotometry, gas chromatography, and COD and TOC measurements. This study revealed that the degradation rate follows the pseudo-first order kinetics. In particular, the degradation assisted by the UV radiation was characterized by the presence of two slopes in the pseudo-first order kinetic profile. A comparative analysis revealed that both the degradation and mineralization of Endosulfan proceed faster and more efficiently under acid conditions (direct oxidation). Moreover, the results confirmed that degradation in alkaline medium takes place through the Endosulfan diol which is the main hydrolysis product of Endosulfan. The O3/UV combined process presented the best performance for degradation showing a maximum removal of Endosulfan. It was proposed a general reaction scheme for the degradation of Endosulfan. The experimental findings concerning the COD and TOC measurements revealed that the COD/TOC ratio remains almost constant regardless the technique used for degradation. Only a slight decrease in the COD/TOC ratio was verified when the UV radiation was applied alone. These findings indicated that the degradation products have a reduced recalcitrance in comparison to the parental compound. Toxicity tests showed that the products of degradation are less toxic when compared to the parental compound. The cost-effective analysis based upon the energy demand revealed that ozonation under dark conditions (when ozone is applied alone) furnished the more promising scenario for degradation of Endosulfan.